2010
DOI: 10.1002/art.27417
|View full text |Cite
|
Sign up to set email alerts
|

Lower expression levels of the programmed death 1 receptor on CD4+CD25+ T cells and correlation with the PD‐1.3A genotype in patients with systemic lupus erythematosus

Abstract: Objective. A genetic polymorphism in the programmed death 1 (PD-1) gene encoding the coinhibitory PD-1 immunoreceptor, PD-1.3A, is associated with systemic lupus erythematosus (SLE). The aim of this study was to assess PD-1 receptor expression in patients with SLE, in comparison with relatives and unrelated healthy controls, and to identify correlations of lower expression levels of PD-1 receptor with the PD-1.3A genotype.Methods. Patients with SLE, patients' relatives, and unrelated healthy control subjects f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 48 publications
1
47
1
6
Order By: Relevance
“…Importantly, the same genotype that was correlated with increased risk to develop the disease also correlated with reduced expression of the PD-1 receptor [23,25]. Despite the lack of data regarding the genetic polymorphism of PD-1 in the current study, the inverse correlation between PD-1 expression and disease activity implies a similar pathogenic role for PD-1.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Importantly, the same genotype that was correlated with increased risk to develop the disease also correlated with reduced expression of the PD-1 receptor [23,25]. Despite the lack of data regarding the genetic polymorphism of PD-1 in the current study, the inverse correlation between PD-1 expression and disease activity implies a similar pathogenic role for PD-1.…”
Section: Discussioncontrasting
confidence: 51%
“…PD-1 polymorphism has been linked to several autoimmune diseases, including systemic lupus erythematosus, ankylosing spondylitis, and multiple sclerosis [22][23][24], indirectly implying a role of PD-1 in the pathogenesis of these diseases. Importantly, the same genotype that was correlated with increased risk to develop the disease also correlated with reduced expression of the PD-1 receptor [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Abrogation of PD-1 signaling enhanced TFH cells numbers and initial immunoglobulin responses, especially early in the GCs response (27). Recent studies had elucidated that the expression of PD-1 in patients with active SLE and RA was significantly lower than the healthy population (28,29). However, our study demonstrated that there was a higher expression of PD-1 in MG patients with thymoma compared with NMG and CTL group.…”
Section: Discussionmentioning
confidence: 44%
“…Polymorphisms in the CTLA-4 gene have been linked to several autoimmune diseases as rheumatoid arthritis (Rodriguez et al, 2002), type I diabetes (Kavvoura and Ioannidis, 2005) and granulomatosis with polyangiitis (Wegener's) (Giscombe et al, 2002;Huang et al, 2000a;Slot et al, 2008;Zhou et al, 2004). In addition several reports show a relationship between these polymorphisms and a reduction in the expression or in the inhibitory function of CTLA-4 (Huang et al, 2000b;Kouki et al, 2000;Kristjansdottir et al, 2010;Ligers et al, 2001).…”
Section: Introductionmentioning
confidence: 94%